Source apportionment and ecological risk of heavy metals in Taihu lake from 2020 to 2022 - Bao, Guangjing; Ji, Chao; Hou, Dawei; He, Yuanbin; Li, Yan; Lei, Dongmei; Fan, Xi (Frontiers in Environmental Science, 2025)
To determine the source apportionment and ecological risk of heavy metals in water from a spatiotemporal perspective, the 7 samples were monitored from 2020 to 2022 in Taihu Lake. The correlation analysis and principal component analysis were employed to identify the sources of heavy metals, and the temporal and spatial characteristics of ecological risk were analyzed using the Mann-Kendall test, mean gravity center, and standard-deviation ellipse. The results indicated an increase in median concentration of heavy metals in the following order: Cd < Pb < Hg < Cu < As < Ni < Zn, These metals were primarily derived from industrial and agricultural activities. Overall, the ecological risks posed by heavy metals were deemed acceptable, with the exception of Hg, which showed considerable potential ecological risk. Furthermore, the potential ecological risk exhibited a significant decreasing trend, with Z-values passing the 95% confidence interval significance test, except for S3. The mean gravity centers of the potential ecological risk were located within an ellipse with center coordinates of (120.2553, 31.3718), major axis of 44,525 m, minor axis of 28,225 m, and a direction of 0.4463°. This study contributes to the enrichment of research perspectives for ecological risk and provides valuable insights for the development of mitigation strategies for heavy metals in Taihu Lake.